Verb Structure in Indonesian - B.R. Suryo Baskoro (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1996)
One of the major problems in studying Indonesian as a foreign language ismastering the verb structure. This is due to the complexity of its affixation. A good and well-formed verb will ensure a good, formal, and acceptable sentence; on the contrary, a lack of affixe where it should be, will give a non-grammatical sentence. Indonesian verbs have two structures: simple and derived verbs.